Development of a web application for a surgical instruments kit inside the traumatology area - Chalarca, Diego Tangarife (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The growing development and evolution of technologies along with major social changes have fostered a reframing in traditional teaching systems where, until now, the professor assumed the leading role.  Nowadays, technology has redefined teaching in different areas and has played a crucial role innovating and transforming educational processes. This research describes the design of a web application as a learning strategy of surgical instruments usage inside the traumatology area. The development architecture was created by using only open source components, making this version freeware under any type of open source software license. Likewise, the state of the art of current surgical instruments available for teaching and training of medical personnel, specifically inside the traumatology area, is presented. This paper presents some final conclusions that should be taken into account when developing this type of applications.